2006
DOI: 10.1016/j.ccr.2006.08.024
|View full text |Cite
|
Sign up to set email alerts
|

p53 family members in myogenic differentiation and rhabdomyosarcoma development

Abstract: The p53 family comprises the tumor suppressor p53 and the structural homologs p63 and p73. How the three family members cooperate in tumor suppression remains unclear. Here, we report different but complementary functions of the individual members for regulating retinoblastoma protein (RB) function during myogenic differentiation. Whereas p53 transactivates the retinoblastoma gene, p63 and p73 induce the cyclin-dependent kinase inhibitor p57 to maintain RB in an active, hypophosphorylated state. DeltaNp73 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 43 publications
(59 reference statements)
6
122
0
Order By: Relevance
“…[104][105][106] Interestingly, it has been demonstrated that cancer cells lacking p53 are protected from oxidative stress-induced by serine depletion in the presence of p73, a p53 family member that has the ability to drive serine biosynthesis de novo 107,108 and to increase the pentose phosphate shunt and nucleotide biosynthesis via G6PD. 109,110 Thus, the p73 overexpression detected in various primary RMS samples 111 may have an important role for oxidative stress resistance.…”
Section: Oxidative Stress Pathwaysmentioning
confidence: 99%
“…[104][105][106] Interestingly, it has been demonstrated that cancer cells lacking p53 are protected from oxidative stress-induced by serine depletion in the presence of p73, a p53 family member that has the ability to drive serine biosynthesis de novo 107,108 and to increase the pentose phosphate shunt and nucleotide biosynthesis via G6PD. 109,110 Thus, the p73 overexpression detected in various primary RMS samples 111 may have an important role for oxidative stress resistance.…”
Section: Oxidative Stress Pathwaysmentioning
confidence: 99%
“…We were intrigued by the pathways enriched in p73-bound loci that are associated with muscle function and development (Table S2). It has been reported that p53, p63, and p73 play at least partially redundant roles in myogenic differentiation and rhabdomyosarcoma formation (12). Alteration of the p53 pathway for example, through a dominant-negative isoform of p73, can block skeletal muscle cell differentiation and promote transformation in vitro (12), and Primers flank c-Jun motifs as assessed by sequence analysis for the same genomic loci as in C. PCR product was resolved by acrylamide gel electrophoresis for reactions using the following DNA samples: genomic input ("I"), DNA purified after ChIP with a c-Jun-specific antibody ("J"), and DNA purified after ChIP with a control, nonspecific, isotypematched antibody ("C").…”
Section: Genes Regulated By Mtor and P73 Classify Rhabdomyosarcomamentioning
confidence: 99%
“…We hypothesized that this role could be related to functions of p73 during myogenic differentiation (12). Although the precise cell of origin remains unknown, studies of molecular translocations provide evidence for mesenchymal stem cells (MSCs) as possible cells of origin for ARMS (15).…”
Section: Genes Regulated By Mtor and P73 Classify Rhabdomyosarcomamentioning
confidence: 99%
“…Methylation-induced silencing of the TAp73 promoter has been found in lymphoblastic leukemias and Burkitt lymphomas (Corn et al, 1999;Kawano et al, 1999). The DNp73 and TAp73 isoforms are co-upregulated in primary rhabdomyosarcomas and tumor-derived cell lines, as compared with normal muscle (Cam et al, 2006). DNp73 isoforms are expressed at high levels in many different tumor types and are related to poor prognosis (Buhlmann and Putzer, 2008).…”
Section: Introductionmentioning
confidence: 99%